Where Literature Fills the Gaps: The Book of Negroes as a Canadian Work of Rememory - Duff, Christine (Studies in Canadian Literature, 2011)
With The Book of Negroes, Lawrence Hill obliges his audience to remember – or discover – that slavery is part of the Canadian collective story. George Elliott Clarke argues that because African-Canadian history is ignored in Canada, African-Canadian writers act as historians to address gaps in the historical record. By addressing a number of such gaps, including the Canadian history of slavery, the slave experience generally, and the female slave experience in particular, Hill, like Toni Morrison, explores how fiction can be a source of truth. Through the voice of Aminata Diallo, the history of slavery is rememoried and rewoven into the fabric of the Canadian historical record, and Hill’s novel is thus part of a larger tradition that includes Afua Cooper’s The Hanging of Angélique: The Untold Story of Canadian Slavery and the Burning of Old Montréal. Hill uses a number of discursive strategies to invest his protagonist with agency, and the story of Aminata addresses some of the strategic silences that were characteristic of the traditional slave narrative genre. With this novel, then, Hill undermines Canadian exceptionalism when it comes to slavery and asserts Canada’s position in the historical and cultural space of what Paul Gilroy calls the Black Atlantic.